2020
DOI: 10.1002/anie.202005882
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Senphos Catalyzed trans‐Selective Cyanoboration of 1,3‐Enynes

Abstract: The first trans‐selective cyanoboration reaction of an alkyne, specifically a 1,3‐enyne, is described. The reported palladium‐catalyzed cyanoboration of 1,3‐enynes is site‐, regio‐, and diastereoselective, and is uniquely enabled by the 1,4‐azaborine‐based Senphos ligand structure. Tetra‐substituted alkenyl nitriles are obtained providing useful boron‐dienenitrile building blocks that can be further functionalized. The utility of our method has been demonstrated with the synthesis of Satigrel, an anti‐platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…A variety of ambiphilic ligands for bifunctional catalysts have been reported so far. [8] Above all, palladium/phosphine-borane catalyst system have been used for many types of catalytic organic reactions, such as hydroboration, [9] cyanoboration, [10] Suzuki-Miyaura coupling, [11] hydrodechlorination, [12] and cross-coupling of acyl chlorides. [13] In addition, our group found that a palladium/phosphine-borane complex is a good catalyst for the allylation and benzylation reactions using allylic and benzylic alcohols.…”
mentioning
confidence: 99%
“…A variety of ambiphilic ligands for bifunctional catalysts have been reported so far. [8] Above all, palladium/phosphine-borane catalyst system have been used for many types of catalytic organic reactions, such as hydroboration, [9] cyanoboration, [10] Suzuki-Miyaura coupling, [11] hydrodechlorination, [12] and cross-coupling of acyl chlorides. [13] In addition, our group found that a palladium/phosphine-borane complex is a good catalyst for the allylation and benzylation reactions using allylic and benzylic alcohols.…”
mentioning
confidence: 99%
“…[11a-e] We recently reported the trans-hydroboration and trans-cyanoboration of 1,3-enynes catalyzed by a 1,4-azaborine biaryl phosphine (Senphos)-Pd complex. [12] An unusual outer-sphere oxidative addition mechanism [13] (a cooperative activation of the 1,3-enyne by LPd(0) and a Lewis acidic boron species) is proposed that introduces the boron group into the alkyne substrate with concomitant formation of a Pd-p-allyl species (vs. a more conventional b-migratory insertion pathway by reactions illustrated in Scheme 1 a-c). Given the known versatility of Pd p-allyl intermediate to achieve diverse functionalizations, [14] we envisioned that new bond connections can be achieved with a variety of nucleophilic boron reagents.…”
mentioning
confidence: 99%
“…Following the pioneering work by Dewar and co-workers in 1958, [3] as well as the recent intensive research by Liu et al, [4] numerous BN-doped aromatic compounds have been synthesized to date. [5] Such studies have not only expanded the family of BN heterocycles but also brought significant advances in materials science [6] and ligand chemistry [7] for transitionmetal catalysis. In addition, BN heterocycles have great potential utility as bioactive molecules.…”
mentioning
confidence: 99%